Conexões docentes: ensino regular e AEE no processo de escolarização de um estudante cego - BERNARDO, Beatriz Figueiredo (2022)
The present study aims to analyze and understand the teaching connections between ESA (Specialized School Service) and the regular classroom with regard to the education of a blind student, as a reflection on the forms and the employment possibilities of the mathematical contents to that student. The subject was to expose the reality of teachers when trying to teach mathematics in an accessible way to the blind student. The research was developed in a qualitative approach with teachers of Regular Education and ESA of a school of the state network, located in the city of Castanhal - PA. It was developed from a field research with the application of a questionnaire and an audio-recorded interview to the teachers. The questions that guide this subject provided a range of questions, mainly due to the lack of information about Braille (Tactile Writing System) for the teaching of Mathematics, which allows including this student in the school curriculum, enabling him to collect necessary information to the point of formulate, resolve and understand matters in a meaningful way. The research data pointed out the difficulties of the mathematics teaching process to this student, the lack of maintenance of materials, in addition to the lack of updating and qualification of the teachers. It is proposed from this study to awaken a new look at the process of teacher qualification, with regard to the inclusion of blind students.